Nanofibras de poli(álcool vinílico) e zeína incorporadas com micronutriente para revestimento de sementes - Natarelli, Caio Vinicius Lima (2024)
The development of seed coatings with a controlled release of micronutrients is extremely important for sustainable and precision agriculture. However, the selection of suitable materials for this purpose represents a challenge, given the complexity in processing immiscible or partially miscible polymers. Techniques for producing nanofibers, such as solution blow spinning, emerge as alternatives for the production of these materials. In this context, the present study aimed to produce nanofibers from poly(vinyl alcohol) (PVA) and zein, two immiscible polymers, and characterize them. In addition to producing nanofibers with incorporated zinc, a micronutrient, so that they act as a coating capable of releasing micronutrients during plant germination and growth. Nanofiber mats were obtained from polymeric solutions with different proportions of PVA and zein, obtaining materials with properties dependent on their formulation. The surface properties of the mats were significantly changed by increasing the zein content (> 37.5%), changing the surface hydrophilicity to hydrophobicity. This increase also reduced the erosion capacity of the nanofibers, while fungal susceptibility was increased. However, the high porosity of the mats (> 80%) provided high permeability to water vapor. With encapsulation efficiency greater than 90%, nanofiber mats incorporated with zinc were produced with a two-step release profile, a rapid initial release followed by a slow release, associated with the zinc reservoir in the nanofibers. Due to their biodegradability, nanofibers were applied as a seed coating, which were subsequently subjected to germination testing. With this, it was confirmed that the released zinc was absorbed by the seedlings, acting as a fertilizer to aid plant growth. Therefore, it can be concluded that PVA and zein nanofibers are a promising material and can be used in several applications, including the proposed one.